RELEVANSI NILAI INFORMASI AKUNTANSI TERHADAP HARGA SAHAM YANG DIMODERASI KONSERVATISME AKUNTANSI - Margareta Chaslim, Carmel Meiden (Jurnal Akuntansi, 2018)
An information content of the published financial statements is said to have value relevance if it is able to revise investor beliefs as reflected in market reaction through stock price changes. Nevertheless, many issues suggest that the value relevance of accounting information has declined, mainly due to the increasing practices of conservatism. This research purpose is to know andÂ  prove the value relevance of accounting information and the impact of conservatism on the value relevance of the manufacturing firms listing in the Indonesian Stock Exchange in the period of 2013-2016. The sample used amounted to 320 observations consisting of 80 companies each year. Based on data analysis techniques with multiple linear regression analysis, it was found that accounting information proved to have value relevance to the stock price, as well as accounting conservatism have a different effect on each accounting information.Keywords: Value relevance, accounting information, stock price, conservatism